THE COMPARISON STUDY OF CRITICAL THINKING SKILL BETWEEN INSTAD LEARNING MODEL COMBAINED CONCEPT MAP AND CONVENTIONAL LEARNING IN STUDYING BIOLOGY - Bowo Sugiharto, Fathoni Hari B, Marjono (P Biologi FKIP UNS Surakarta, 2015)
The purpose of the research was to know there was difference of critical thinking skill between INSTAD learning model combained concept map and conventional learning in studying biology of second grade students SMA Negeri 4 Surakarta specify on sains in 2012/2013 academic year.Quasy experiment and post-test only with nonequivalent group design were applied in this research. The populations were the second grade students of SMA Negeri 4 Surakarta specify on sains in 2012/2013 academic year. It was 188 students. The samples were 62 students that taken using cluster sampling technique in the form of two classes and placed into experimental class and comparitional class. The critical thinking skill information was determined by essay test with Facione?s critical thinking skill indicators. The demographic information was collected by a researcher ?made questionnaire and observation sheet. T-test was used for data analysis.The t-test?s value was -4,926 and significance value was 0,000 (lower than 0.05). The syntax of INSTAD learning model combained concept map had done well. Students agreed that INSTAD learning model combained concept map could train their critical thinking skill. There was difference of critical thinking skill between INSTAD learning model combained concept map and conventional learning in studying biology of second grade students SMA Negeri 4 Surakarta specify on sains in 2012/2013 academic year. Keyword: critical thinking skill, INSTAD learning model combained concept map, conventional learning